Measurement of the Upper Tropospheric Density and Temperature Profiles in Hanoi Using a Raman Lidar - Tuan, Nguyen Xuan; Trung, Dinh Van; Binh, Nguyen Thanh; Hai, Bui Van (Communications in Physics, 2016)
The nitrogen molecular density and temperature profiles of the upper troposphere are measured by a Raman lidar system in Hanoi over the range from 3 km to 19 km. The spatial and temporal resolutions of profiles are 60 m and 1h, respectively. The nitrogen molecular density profiles are directly calculated from the range-corrected lidar signal. The temperature profiles are derived from the molecular density profile based on the assumptions of the hydrostatic equilibrium, the ideal-gas law and a fixed nitrogen molecule ratio in the atmosphere. The results of our lidar measurements show good agreement with the MSISE-90 atmospheric model. The maximum errors of density and temperature measurements are 6% and 7%, respectively. We estimated the height of tropopause in Hanoi about 16 km from the derived temperature profile. The measured density and temperature profiles from this Raman lidar can be used for studying the trends and characteristics of the upper troposphere in Hanoi.